Administrative management and Transparency in interventions. The "Reconstruction with changes" post natural disaster in Cura Mori, Piura - Delgado Vera, Gloría María (2022)
There is no greater citizen demand for the presence of the State, as in situations of natural disasters. An exemplary case was the devastation of the Cura Mori district in the Piura region because of the Coastal Child Phenomenon in 2017. The administrative management of the State is the response to these demands through its interventions, which for more than 4 years have implemented a plan reconstruction. However, for the perception of the residents of Cura Mori, public management has not advanced according to the needs and emergencies of the basic infrastructure demanded by the population. Given this, this article set out the general objective of determining the relationship between the Administrative Management of the New Public Management and the transparency in the progress of the interventions for the “Reconstruction with changes” in the district of Cura Mori-Piura 2021. Research of a basic, correlational, and quantitative non-experimental type, which applied two surveys to 376 inhabitants of Cura Mori: one for each variable. The results demonstrated, applying Pearson's X² test, the existence of a relationship between both variables. Since, the resulting X² (155,302)> critical X² (21.3); also, the significance value (0) <α = 0.05. This implies a level of bilateral significance correlation of 0.05 and confidence of 5%, fulfilling that p <.05 (0 <.05), showing a high positive relationship between the variables.